The Pancasila Student Profile: Insights from Islamic Religious Education Perspectives - Afwadzi, Benny (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
The Indonesian education system faces various challenges, including a decline in respect for teachers, incidents of student brawls, and numerous cases of intolerance. In response, through the Ministry of Education and Culture, the Indonesian government has introduced the Pancasila Student Profile as a framework within the education system. This article aims to analyze the concept of the Pancasila Student Profile from the perspective of Islamic Religious Education (IRE). Using a qualitative approach and a library research method, the author collected literature from various digital platforms. The findings indicate that the Pancasila Student Profile comprises six dimensions: faith and devotion to God Almighty and noble character, global diversity, cooperation, independence, critical reasoning, and creativity. The study reveals that the Pancasila Student Profile is compatible with IRE, as both aim to educate and improve students' character and morals. Among the six dimensions, faith and devotion to God Almighty and noble character, as the first dimension, is the most directly related to IRE, though the other dimensions are also relevant. However, in implementing the Pancasila Student Profile, educators should continue to uphold valuable Islamic traditions, such as recognizing the crucial role of educators in the learning process.